Palco de disputas e disputas pelo palco no "país do forró" - Paulino, Thiago (2017)
Forró is a cultural production which is connected to tradition and today is inserted in consumer logic. This dual relation (tradition/cultural consumption) demonstrates the reality of a transitional world in which social actors compete for spaces in search of recognition and survival. This paper is about the disputes among those that produce the traditional forró, commonly known as forró-pé-de-serra. This research shows a part of the trajectory of the forró of Sergipe, its history and constructed meanings. Meanings that already start to to be confrontational in the definition of what is forró, from the place it speaks and the terminologies used (pé-de-serra, electronic, college). To observe the actors of forró-pé-de-serra, is also to observe how they relate and position themselves with otherness. The research sought, using biographies, interviews and perceptions of the social spaces of forró (arraiais, public and private events) to understand how the music expresses a social identification, of belonging and, at the same time, conflicts and disputes inherent in these processes. We observed at this point two types of dispute: one more concrete and direct in which the forró artist tries to make his music present on big event stages financed by the state, as the Forró Caju; and a wider one that sometimes crosses even the passing of the years, connected to sensory disputes, to circumstances and to different positions among the social actors. In respect to the scope of the first dispute, to be on stage to make your own music known is fundamental to the production chain and consumption of forró. However until the moment of contact of the artist and the audience, there are steps where power relations pass through, that materialize in actions like the definition of the criteria of choosing artists, the adopted behaviours to attain a space in the June Festivities. Among other authors, we adopt the theoretical perspective of Elias to observe the power in the configurations and relations of interdependence. The public manager, whether he is mayor, governor or an event director, needs the artist to make the “show go on” and the artist, in turn, needs the stage to express his art and world vision, but also to have his performance consumed.